Characterisation of Drosophila melanogaster mutated for all genes of the Sirtuin family - Pekáčová, Aneta (Jihočeská univerzita, 2019)
The aim of my study was to create a Drosophila line lacking the expression of all Sirtuin genes, check its developmental phenotype and characterise its response in stress conditions. The flies had bigger weight than controls, they had decreased fertility and fecundity and they developed more slowly. They showed a trend towards increased resistance to chill coma, but they did not show a significant difference in starvation or oxidative stress assay. Its effect on lifespan is being investigated.
Characterisation of Drosophila melanogaster mutated for all genes of the Sirtuin family
Keywords: sirtuin; drosophila; mutation; characterisation; sirtuin; drosophila; mutation; characterisation